Rekonstruksi Metode Penafsiran al-Qur'an Menurut Muhammad Arkoun - Alhini Zahratana; Nur Khovivah (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2022)
Revelation of Qur'an is a central issue in the Muslim tradition that for Arkoun needs to be reevaluated because it has caused Muslims to be dogmatic. the urgency of the reconstruction of the Qur'anic interpretation comes from Arkoun's assumLption that the meaning of the Qur'an which is currently still circulating is no longer sacred as it was at the time of the Prophet, Arkoun considers that the revelation in the form of the Qur'an has been manipulated by the scholars since the death of the Apostle, he has undergone changes in terms of meaning due to transmission from one human to another. Therefore, so that Muslims do not appear to be clumsy with the existing doctrine of meaning, the interpretation needs to be a reconstruction of the interpretation of the Qur'an using contemporary knowledge that is in accordance with the times. Arkoun formulates western social sciences with Islamic knowledge that he learned in the area where he lives and teaches with the hope that a new method of interpretation will emerge that has never been done by previous Muslim scientists. This is believed to have an impact on shifting the role of the previous method of interpreting the Qur'an.